The use of Modern Official Documents in the early Modern Siam: A Case Study of the Department of the Royal Secretariat during the Reign of King Chulalongkorn - Hin-on, Rewat (Journal of Arts and Thai Studies, 2024)
Objectives: This academic article aims to study the relationship between the use of official documents and the public administration of Siam during the beginning of King Chulalongkorn's reign, through the work of the Royal Secretariat Department. Methods: The study employed historical research methods, involving the examination of primary and secondary documents related to the use of official documents within the Royal Secretariat Department during King Chulalongkorn's reign. Results: The study found that the Royal Secretariat Department held primary responsibility for selecting, submitting letters, and preparing reports. This process represented a modernization of government documentation, necessitating planning and improvement, and served as a crucial foundation for subsequent developments in modern government documentation usage. Application of this study: This article is beneficial for those interested in the history of Siam's public administration during King Chulalongkorn's reign, particularly regarding the utilization of official documents, in order to facilitate further educational advancements.